THE USE OF QUIPPER SCHOOL AS AN ONLINE LEARNING MEDIUM: - Pertiwi, Rasyita; Jabu, Baso; Samtidar, Samtidar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
This research aims to find out students’ perception towards the use of Quipper School as an online learning medium and what are the advantages and disadvantage of Quipper School as  a  learning  medium.  This  research  applied  a  descriptive  qualitative  method.  The  data collection in this research was conducted by interviewing 30 students of SMAN 8 Makassar as  the  participants  of  this  study.  The  result  of  this  research  found  that  there  are  several pluses such as: Free access video, show the right answer after the wrong one, ready to study material, easy to use and understand, concise and complete video explanation, has a feature that support the students to train their self with the tasks, quiz, and summary, and repeatable answer.  For  the  minuses,  the  minuses  of  this  application  are  network  problem,  pictures problem, freeze or bug, unclear explanations, and language problem. It can be concluded that  Quipper  School  is  easy  to  access  and  use,  cost  free,  and  useful  for  support  online learning. Keywords—Quipper School, Students Perception